An Analysis of Loan Loss provisioning system in Chinese Banking - Zhang, Jingsi (2017)
After the global financial crisis, the regulators and academics around the world began to examine the financial supervision system. They considered that the pro cyclicality of a financial system is one of the major causes of the financial crisis, and tried to build a counter cyclical mechanism to relief risks. Loan loss provisions are based on the evaluation of loan losses and are an important measure banks used to resist loan loss risk. In theory, the loan loss provisions allow banks to confirm losses in advance, therefore they can be seen as a significant tool of risk prevention. However, the internal mechanism of loan loss provision leads the provisions to have the characteristic of pro cyclicality. On the basis of the incurred loss model, banks are likely to reduce the loan loss provisions to remain high level of lending under the drive of high profits in economic upward period, however in the economic downturn, the provisions made before can not make up for the high loan losses, therefore, banks would increase the loan loss provisions resulting in a decrease of bank lending and profitability as well as an increase in economic cyclical fluctuation. In practice, the dynamic provisioning system is a counter cyclical instrument introduced to remit the pro cyclical effect caused by the original backward-looking model. On the basis of relevant literature and the latest financial data of Chinese banking industry, this paper made an empirical analysis of the pro cyclicality of Chinese banking loan loss provisions and its determinants by means of the generalized method of moments and comparatively studied the dynamic provisioning systems of international main countries at present. It is found that the non-discretionary component of loan loss provisions in Chinese banks is pro cyclical and the discretionary loan loss provisions have an obvious motivation of income smoothing, but the capital management hypothesis is not accepted. The aim of this paper is to discuss the loan loss provisioning system of Chinese banks and analyze its pro cyclicality, hoping to provide some advice on establishing dynamic provisioning system and improve the monitoring of bank loan loss provisions.